Social cognition and interpersonal violence - Megan Kang; Kathryn Edin; Jens Ludwig; Timothy Nelson; Sendhil Mullainathan (Proceedings of the National Academy of Sciences, 2026)
Why do some people resort to violence while others in similar circumstances do not? Drawing on 99 in-depth interviews with men from high-violence Chicago neighborhoods who participated in a community violence intervention, we examine how past exposure to violence shapes the social cognitions that influence future involvement in violence—through the schemas and scripts people use to interpret social situations and guide behavior. We identify three specific social cognitions that respondents associated with violence: misconstruing ambiguous cues as threats, defaulting to a narrow set of behavioral responses, and attributing violent behavior to fixed personal traits rather than situational factors. Respondents reported that participation in the program’s cognitive behavioral component shifted these social cognitions in ways they associated with reduced violence involvement. The consistency of these self-reports combined with the program’s experimental impacts suggest the hypothesis that these specific social cognitions could play an important role in violence and may be modifiable through intervention.